Cashless Transaction Myths and Reality in the Indian Economy:A Case Study - Borthakur, Munmi (Indian Journal of Computer Science, 2018)
Objectives: This paper discusses the general overview of cashless transactions using digital payment systems. It Includes highlights of the impact of demonetisation on non-cash mode of payments. Methods: The method aims at classifying the modes of payments and providing a definition of the concept and how data mining can be used to gain insight from this huge amount of data and Â to enhance the performance of some of the core business processes in the banking sector. Findings: Adoption of digital payment system in accordance with cashless transactions appears to have facilitated a reduction in the usage of paper-based mode and increasing electronic modes of payment. This in turn increases the quantity of data in the various repositories(databases). Data mining techniques can be used to gain insight of these data. Application/Improvements: The study highlights the usage of cashless modes and how it can take individuals as well as economies a step forward.